2013
DOI: 10.1371/journal.pone.0061031
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Inhibits Primary Root Growth by Reducing the Length of Meristem and Elongation Zone and Decreasing Elemental Expansion Rate in the Root Apex in Arabidopsis thaliana

Abstract: The inhibitory effect of ammonium on primary root growth has been well documented; however the underlying physiological and molecular mechanisms are still controversial. To avoid ammonium toxicity to shoot growth, we used a vertical two-layer split plate system, in which the upper layer contained nitrate and the lower layer contained ammonium. In this way, nitrogen status was maintained and only the apical part of the root system was exposed to ammonium. Using a kinematic approach, we show here that 1 mM ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
114
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(133 citation statements)
references
References 42 publications
18
114
1
Order By: Relevance
“…For instance, PR elongation is strongly inhibited by systemic calcium deficiency, whereas LR elongation is even slightly induced (Gruber et al, 2013). Likewise, NH 4 + concentrations that stimulate LR formation concomitantly suppress meristem size of the parental root (Lima et al, 2010;Liu et al, 2013b). As suggested by the specific effect of mild and prolonged nitrogen deficiency in TAR2-regulated or CLE-CLV1-regulated LR elongation (Araya et al, 2014;Ma et al, 2014), a dose-dependent or pronounced morphological response in LRs may rely on not only the size of a signal but also, the cell type-specific expression pattern of receptors translating these systemic signals into developmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PR elongation is strongly inhibited by systemic calcium deficiency, whereas LR elongation is even slightly induced (Gruber et al, 2013). Likewise, NH 4 + concentrations that stimulate LR formation concomitantly suppress meristem size of the parental root (Lima et al, 2010;Liu et al, 2013b). As suggested by the specific effect of mild and prolonged nitrogen deficiency in TAR2-regulated or CLE-CLV1-regulated LR elongation (Araya et al, 2014;Ma et al, 2014), a dose-dependent or pronounced morphological response in LRs may rely on not only the size of a signal but also, the cell type-specific expression pattern of receptors translating these systemic signals into developmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Valentine et al [96] also reported, that NH4 + fed AM roots had lower numbers of vesicles and arbuscules than NO3 − supplied roots. An excess of NH4 + as sole N source is often considered to be toxic for plants, and inhibits root growth [97].…”
Section: Uptake Of Inorganic N Sourcesmentioning
confidence: 99%
“…The regulation of auxin distribution in roots controls both cell division and elongation [Blilou et al, 2005]. Research indicates that ammonium influences root growth by reducing both the meristem and elongation zones and decreasing the elemental expansion rate in the root apex [Liu Y et al, 2013].…”
Section: Comparison Of Chromatin Epigenetic Modificationmentioning
confidence: 99%